Correlation between McIssac Score and Throat Swab Culture in Patient Presenting with Acute Tonsillitis - Bhandari, Shama; Paudel, Dhundi Raj; Gurung, Kishor (Journal of Nepalgunj Medical College, 2021)
Introduction: Tonsillitis is inflammation of tonsils which is characterized by various signs and symptoms with sore throat being the most consistent symptom. The condition is mostly caused by bacterial infection with Streptococci being the most common bacteria. McIssac scoring technique is clinical symptoms based scoring method designed for diagnosing streptococcal tonsillitis.Aims: To find out the association between McIssac Score and beta hemolytic streptococcal infection in acute tonsillitis.Methods: This hospital based, prospective study was carried out in the Department of ENT, Nepalgunj Medical College from July 2020 to June 2021. Patients were scored as per McIssac score. The specimens were collected from the tonsillar surface using sterile cotton swabs and subjected for culture and sensitivity.Results:The most common affected age group was 21 to 30 years (46%). Females were affected more commonly (57%). The most common organism isolated in the study was Group A beta hemolyticn Streptococcus (48%), followed by Pseudomonas (10%), Enterococcus (9%) and Klebsiella (8%) and no organisms were isolated in 25% of the patients. It was observed that high McIssac score was associated with higher chance of having positive beta hemolytic streptococcal infection. Out of 48 group A beta hemolytic streptococci culture positive patients 18(37.5%) patients scored 3, 9 (18.75%) patients scored 4 and 7(14.5%) patients scored 5.The most common antibiotic effective against group A beta hemolytic srtreptococci was ceftriaxone in 25(72.9%), followed by amoxyclavulinic acid in 20 isolates (41.6%) and amikacin in seventeen (35.4%) isolates.Conclusion: The correlation between throat swab culture and McIssac score emphasized that this clinical scoring system aid in early diagnosis of group A beta hemolytic streptococci tonsillitis.